Analisa Dampak Metode Full Costing Terhadap Harga Pokok Produksi: Literature Review Dipublikasikan di Sinta Tahun 2019-2023 - Septian Adiguna; Sari Lestari; Nani Mulyani; Shofia Marwah; Rachmat Agus Santoso (CV. Ulil Albab Corp, 2024)
In the calculation of the cost of production between the Full Costing method and other methods, particularly those commonly used by micro, small, and medium enterprises (MSMEs), Full Costing includes all production costs, including factory overheads, while other methods only take into account variable costs such as raw materials and direct labor. The research findings indicate that the use of Full Costing provides a more accurate and comprehensive overview of production costs, enabling more precise pricing decisions. Appropriate pricing is crucial for maintaining competitiveness and profitability. The implementation of Full Costing can help companies make better decisions in managing production costs and improving market performance. Thus, this research highlights the importance of the Full Costing method in business decision-making to enhance profitability and product competitiveness